Effects of single dose low-level laser therapy, on pain and healing of extraction socket after extraction of premolars in orthodontic patients - Karim, Meenaz (2023)
Tooth extraction for orthodontic purposes is a common procedure. However, extractions, just like other surgeries carry some complications and risk like pain, swelling, infections, and dry socket. Non-steroidal anti-inflammatory drugs (NSAIDs) are preferred medicines to reduce post-extraction pain, but it may have systemic effects. Low-level laser therapy (LLLT) has been found effective in decreasing the post-extraction pain and acceleration of wound healing after third-molar extraction. Orthodontic forces initiate osteoclastic activities in the alveolar bone which causes mobility of the tooth which also eases the extraction and reduces post-extraction pain, but it has not been investigated. The purpose of this research was to evaluate the effect of single dose of LLLT on the pain and healing of extraction socket before alignment and levelling stage, after initiation of orthodontic treatment. Forty-four Pakistani patients, age between 12 to 18 years who needed pre-molar extraction for orthodontic treatment were selected, which were then divided into 2 groups (A and B). Both groups had experimental (Ae, Be) and placebo sides (Ap, Bp), allocated randomly for split mouth design. Group A underwent extractions first, then orthodontic treatment. However, group B underwent extractions after alignment and leveling of teeth. Gallium-Aluminum- Arsenic diode laser (continuous-mode, wavelength 940nm) was applied on 6points buccally and palatally, 1cm apical to the extraction socket, immediately after extraction. Irradiation was applied for 30seconds at each point, emitting energy of 3joules. After extraction, pain was recorded for a week with numeric rating scale and wound healing was assessed clinically at baseline, 2nd, 7th and 15th day. SPSS version 22.0 was used to analyze the data. Experimental and placebo sides were compared to observe the effect of LLLT on pain and wound healing, while inter group comparison was made to see the effects of prior engagement of tooth with the arch-wire, on pain and wound healing. Non-parametric Mann Whitney U test and Krusker Wallis test were applied to compare the results amongst all the groups. Group A experienced significantly more pain when compared with group B (p<0.05). The difference in pain between experimental and placebo sides in both the groups was insignificant. No significant difference was observed regarding wound healing among groups. In conclusion, single visit application of LLLT did not reduce the post-extraction pain and did not affect the extraction wound healing in orthodontic patients. Prior engagement of pre-molars reduced the extraction pain, however wound healing remained unaffected.